Liquid journalism: trends in amplification of the field - Rublescki, Anelise; Silva, Alexandre Rocha da (Brazilian journalism research, 2012)
This article derives from a broader investigation which discusses the metamorphoses that are established for the mediation and the capability for processing of the news in the culture of the convergence and digitalization. As a direct result of the investigation seven trends to enlarge the boundaries of the field are highlighted: 1) diffuse journalism, 2) residual recovery journalism, 3) deepening of journalism in collaboration, 4) predominance of news centered on the reader, 5) more value given to local content, 6) personalization of the fruition of the news, and 7) plurality of voices and framings with regard to the same fact. Methodologically, it is a theoretical and critical article, developed from review of the literature and empirical observation.